Development of Sadda Pind as a Cultural-Based Tourist Attraction to Increase Community Economic Growth in Amritsar, Punjab, India Post Pandemic Covid-19 - Muntaha, Baitul Ma’mur (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Sadda Pind is a punjabi cultural living village museum located in the holy city of Amritsar. The purpose of this study is to identify the potency of Sadda Pind to improve the economy of the surrounding community post the Covid-19 pandemic. This type of research is conducted by using qualitative research, while the technical analysis used in this research is using SWOT analysis. As a tourist attraction that is managed by the private sector, the management that is presented is very good and organized. However, in its application, there are still many deficiencies that need to be addressed by the management of Sadda Pind. The results of this study indicate that improvements are needed in the implementation of tourism activities post the Covid-19 virus pandemic so that traveler are no longer reluctant to travel and increase visits so that it can increase the economic growth of the surrounding community.